Preparation and thermal degradation of poly(p-substituted phenacyl methacrylates) - Coskun, M; Soykan, C; Ahmedzade, M; Demirelli, K (Elsevier Sci Ltd, 2001)
The preparation and thermal degradation of two poly(p-substituted phenacyl methacrylates), poly(p-bromophenacyl methacrylate) [poly(BPMA)] and poly(p-methoxyphenacyl methacrylate [poly(MPMA)], are described. The monomers produced from the reaction of corresponding phenacylchlorides with sodium methacrylate, were polymerized with AIBN as initiator. The monomers and their polymers were characterized by IR, H-1 and C-13 NMR. Thermal degradation of the polymers has been studied using a system consisting of a degradation tube, with a condenser for product collection, a gas phase IR cell and a rotary pump, and by thermogravimetry (TG). Product studies were performed by IR, GC-MS, H-1 and C-13 NMR. Thermal degradations of these two poly(p-substituted phenacylmethacrylates) to give volatile products, begin at about 250 degreesC. The degradation produces anhydride ring structures in the chain at about 260 degreesC. A mechanism of degradation showing the formation of some products is discussed. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: thermal degradation; phenacyl methacrylates